Pemanfaatan Fly Ash Bottom Ash dan Tawas Untuk Menetralkan Air Asam Tambang - Gregorius Bryan Giftin Samosir; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2021)
PLTU X uses coal as its fuel. The impact of the use of this coal produces 150 – 200 tons of fly ash bottom ash (FABA) waste every day and is pilled up in the ash disposal. This study aims to utilize FABA, alum and mixture of both to neutralized acid mine drainage. Acid mine drainage used as the object of this research is taken from CV. Air Mata Emas Sawahlunto which had pH 3.72. This experimental test was carried out by varying the mass of FABA, alum and mixture of FABA alum to neutralized acid mine drainage. The result of this research on mixing 200 ml of acid mine drainage water samples which had pH 3.7 2 with various FABA masses, it was found 1 gr of FABA could increase the pH of acid mine water to 7.3. It isn’t recommended to use alum for neutralizing acid mine drainage because an increase mass of alum actually makes acid mine drainage more acidic. For neutralizing acid mine drainage using a mixture of FABA and alum, the ratio of both of 5.3 : 0.5 can neutralized acid mine water with pH of 3.72 to 7.71. The mixing of FABA and alum can also accelerate the deposition of FABA used, so that neutral acid mine water can be drained directly outside the mine area. Keywords: Coal, Fly Ash Bottom Ash, Acid Mine Drainage Neutralization, pH, alum.